Effect Of Return On Equity, Earning Per Share, Debt To Equity Ratio On Stock Return - Rambe, Nadiva Aura Innaya; Imam Muarif; Mangasi Sinurat; Willy Cahyadi (Jurnal Ekonomi, 2024)
There are fluctuations in stock returns in transportation and logistics subsector companies listed on the Indonesia Stock Exchange (IDX) during the 2019-2022 period. This study aims to examine the effect of Return on Equity (ROE), Earning Per Share (EPS), and Debt to Equity Ratio (DER) on the stock returns of transportation and logistics companies listed on the IDX for the 2019-2022 period. This study uses secondary data obtained from the IDX's official website and the company's financial statements. The research sample was selected using the purposive sampling technique, resulting in 13 companies as a sample. Data analysis was performed by panel data regression using EViews 10 software. The results show that ROE, EPS, and DER do not have a significant influence on stock returns, either partially or simultaneously. Financial performance measured through ROE, EPS, and DER did not affect the return on shares of transportation and logistics companies listed on the IDX in the study period. There are other factors that also affect such as macroeconomics and political risks that have a greater effect on the performance of stocks in this subsector.